Repentance Dance Work - Ignasius Herry Subiantoro; Nur Rochmat (Pascasarjana ISBI Bandung Conference Series, 2025)
The theological idea of this writing takes the theme "Repentance" as a symbol of beauty. Saint Augustine was a philosopher who relied on logic/reason and did not believe in the glory of God as the source of life. The writing on the wall of his room and the lyrics of the song "Symbol" became the core of his statement of repentance. It was then transformed into a symbol of the beauty of Batak Toba Repentance dance work. It Aims to provide an understanding of the aesthetic form of philosophical ideas about the beauty of human relationships with God, nature and each other. This article studies Von Balthasar's Theological Aesthetics, what is good (bonum), true (vorum) and beautiful (pulrum) are attributes of God, bringing joy to life. The Repentance Dance is a symbolic representation of the story of Saint Augustine, taking the kinesthetics of Batak traditional dance as the beauty. Keywords: Repentance Dance; Batak Toba Traditional Dance, God Symbol.